Multicultural Education of EFL Classrooms in Indonesian Islamic Higher Education: Challenges and Strategies - Deiniatur, Much; Hasanah, Uswatun (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2024)
Multicultural education in English Language Teaching (ELT) has gained significant attention, although challenges still persist in its classroom implementation. Therefore, this study aimed to investigate challenges and strategies associated with implementing multicultural education in English as a Foreign Language (EFL) classes within Islamic higher education institutions in Indonesia. A case study method was used, and semi-structured interviews were conducted with six teachers actively involved in EFL teaching to explore the complexities and nuances of integrating multicultural education in this context. The results showed various challenges, including the need to balance cultural sensitivity with standardized curriculum requirements, addressing potential resistance or discomfort among students during discussions of culturally sensitive topics, and mitigating resource limitations hindering comprehensive multicultural education. Furthermore, teachers emphasized the importance of enhancing mutual respect, improving intercultural understanding, and integrating diverse cultural content into the curriculum. Future studies were recommended to emphasize collaborative efforts, institutional support, and ongoing professional development to help teachers adapt teaching methods effectively. Despite limited resources, teachers remained committed to creating inclusive learning environments that prepared students to become proficient English speakers and global citizens capable of appreciating and thriving in a diverse world. In conclusion, this study provided valuable insights for teachers, institutions, and policymakers to improve multicultural education in similar educational contexts.